La emigración gallega a México, 1878-1936 - Villaverde García, Elixio (1998)
This thesis studies Galician men and women in the Mexican Republic from 1878 to 1936. After the first chapter: Historiografía, Metodología y Fuentes (Historiography, Methodology and Sources) the following two chapters deal with the socio-economic and political conditions of the source country, Galicia, the Mexican post-independence expulsions and the inmigratory and colonising politics between 1821 and 1877. Chapter 4: El Papel Esencial de las Cadenas Migratorias y las Redes Sociales (The Fundamental Role of Migratory Chains and Social Networks) points at the arrival throughout "the Porfiriato" of certain relevant pioneers. Herein we aim to establish, from these pioneer settlements, the dynamics of some especially significant migratory chains. Chapter 5: Caracterización Cuantitativa y Cualitativa de esta Corriente Migratoria (Quantitative and Qualitative Characteristics of this Migratory Flow) taking as starting point the mexican R.N.E. (National Register of Aliens) analyses in depth, and within 5 subperiods, the following features: provenance municipalities and provinces, towns and cities of residence, age and gender groups, socio-professional activities, port of entrance into the country, linguistic competence, marriage habits, religion etc. In Chapter 6 we study the social and economic insertion of some pioneers and certain especially paradigmatic second generation emigrants. We also analyse associationism with a special emphasis in the Centro Gallego de Veracruz (The Veracruz Galician Centre) founded at the end of the 19th century and the Orfeón Gallego de México (The Galician Choral Society of México) and the Centro Gallego de México (The Galician Centre of México) founded at the beginning of the 20th. In the Conclusiones (Conclusions) we summarise the basic contributions of the current research: 1.- The change from the initial coastal and urban emmigration to a generalised inland rural emigration found already in the twenties; 2.- The previous seasonal migratory tradition and culture as a basis of this transoceanic emmigration; 3.-The awareness of a minimal schooling before sailing and of a further updating or recycling in México; 4.- A greater tendency towards socio-professional insertion within commerce, starting as employees, and, above all, as peddlers or "aboneros"; 5.-The intense operativity of migratory chains anel social networks in Galicia and Mexico as a strong mechanism which manages and lends dynamism to this migratory flow; 6.- The exogamy of the pioneers and the endogamy of the greater emmigration; 7.- The role of living quarters, especially that of the neighborhoods, of the same type of job and associationism as elements which maintain the identity of the group; 8.- The verification of the hypothesis of Cuba-Mexico re-emigration; 9.- As a consequence of this emigration, a moderate optimism; 10.- An overhead quantification as regards the stock of 4468 immigrants inscribed in the R.N.E. an undergnote [?] as regards the 25675 migrants of the presumable mean flux of Spanish and Mexican statistic.